BEHAVIOR OF FUNDING AND LENDING PRICING OF INDONESIAN BANKS: EVIDENCE FROM AGGREGATE POST CRISIS DATA - Soenartomo Soepomo; Moch. Doddy Ariefianto (University of Merdeka Malang, 2013)
The study aimed to reveal the behavior of lending and funding pricing (deposit interest rate and loan interestrate) of Indonesian banks after the great crisis in 1998. Specifically the research design aimed to uncover theform of interaction (state of equilibrium) and factors that might influence the state of equilibrium. We used amodel developed by Niehans (1978) and De Grauwe (1982) as a point of departure to address the researchproblem. There were 12 variables used in a simultanous equation econometric model that would be estimated byusing 4 different techniques namely GMM TS, GMM CS, 3SLS and SUR. Two variables namely price ofdeposit and price of loan were treated as endogenous. We also considered the impact of deposit insuranceadoption that was took place in September 2005.The empirical findings showed that the slopes of DD and LLequation were largely consistent with the hypotheses. The parameters were positive and statistically significant.However the numerical value of LL slope that was greater than the other one and comparable to DD slopehad raised a concern for the stability attainment. The most important variables (based on their magnitude andstatistical significance) found to affect the constellation were business prospect, system size, exchange rate,operational cost and profitability. In the second tier of importance, we found that monetary policy instruments(policy rate differential and base money supply), quality of loan, capital and total liquidity affected the systemin various degrees.